The processing of familiar English L2 phrasal verbs in neutral and biased sentence contexts - Yu, Jianyao; Wang, Siya; Zhang, Ping; Chen, Tai’an (Frontiers in Psychology, 2025)
This paper addresses an important psycholinguistic question: whether L2 learners preferentially process phrasal verbs (PVs) literally or figuratively, irrespective of context and proficiency levels. Our primary aim was twofold: first, to investigate how familiar English L2 PVs are processed—whether literally or figuratively—and secondly, to explore this across different contexts (neutral, literal bias, figurative bias) and proficiency levels among learners. Drawing on existing literature, we tentatively hypothesized that while learners might activate literal meanings early in processing, figurative activation could dominate later stages as far as familiar PVs are concerned. Familiarity with PVs may be critical across proficiency levels in driving PV processing. What’s more, the preferred meaning may be bootstrapped in supporting context, but the less preferred meaning is likely suppressed even with context boost. To achieve these objectives, an eye-tracking experiment was conducted with intermediate and advanced Chinese English L2 learners. Participants read context sentences containing PVs followed by a visual word search task to assess PV meaning activation at early, late and further delayed stages. Statistic analysis revealed that no consistent interpretation of PVs as literal or figurative in the time course emerged. However, in sentence reading, we observed faster late meaning activation in both literal and figurative contexts than in the neutral context, and delayed preference for figurative interpretation in the post-PV region. Meanwhile, in visual word search task, meaning activation was context-dependent and fluctuated over time, indicating temporal dynamics in processing. Last but not least, proficiency ranging from intermediate to advanced levels did not significantly impact processing when PV familiarity was achieved. Our findings suggest that teaching strategies should focus on enhancing learners’ ability to recognize figurative meanings. This approach could improve reading comprehension by promoting learner awareness of PVs as whole lexical units. In conclusion, this study enhances our understanding the mechanisms underlying L2 PV processing dynamics and provides actionable insights for language acquisition strategies, thus contributing valuable knowledge to the field of second language processing and learning.